Revision of the loach genus Claea Kottelat, 2010 (Teleostei: Nemacheilidae) in China, with a description of a new species from the Chang-Jiang basin - Zhang, Chu-Yi; Luo, Pan; Huang, Feng; Zhang, E. (Zootaxa, 2024)
A taxonomic revision of the nemacheilid genus Claea from China is provided based on molecular and morphological data. Three species are identified in this genus: C. dabryi (type species), C. wulongensis (a species originally recognized in Triplophysa), and C. minibarba sp. nov., here described from the mid-upper Chang-Jiang basin in northwestern Hubei Province, South China. This new species differs from the two congeneric species in having a deeper body, further from C. dabryi in having shorter outer rostral and maxillary barbels, and further from C. wulongensis in possessing a higher count of vertebrae, a deeper caudal-peduncle, and a narrower interorbital space. Its validity is corroborated by its monophyly recovered in a mitochondrial cytochrome b gene-based phylogenetic analysis and its significant genetic divergence of this gene with the two congeneric species.